A criminologia no Brasil ou como tratar desigualmente os desiguais - Alvarez, M. C. (Iuperj, 2002)
In this article we discuss how the ideas of Cesare Lombroso (1835-1909) and his followers were incorporated into the intellectual debate in Brazil in the late 19(th) and early 20(th) centuries. By specifically analyzing the intellectual production of Brazilian legal scholars and jurists of the time - who drew on ideas from criminology to conceive Brazilian society and to propose legal and institutional reforms - we attempt to demonstrate how these ideas contributed to the elaboration of differentiated forms of legal and penal treatment for certain segments of the population.
Criminology in Brazil, or how to treat the unequal unequally
Keywords: Cesare Lombroso; criminal anthropology; criminology; intellectuals; legal scholars; criminal justice; citizenship